Effects of water-to-cement ratio and curing age on microscopic creep and creep recovery of hardened cement pastes by microindentation. (October 2020) - Liang, Siming; Wei, Ya
Abstract: This study is dedicated to measuring the microscopic creep and creep recovery of hardened cement pastes by microindentation technique. The influence of water-to-cement ( w / c ) ratio and curing age of cement pastes on the micro creep and creep recovery was assessed. It is found that more than 60% of the recoverable creep of the cement pastes used in this study evolves over the loading stage. Recoverable creep is also observed during the holding stage, which only accounts for 7.2%–15.9% of the creep deformation over the holding stage. Both creep and creep recovery of cement pastes at micro scale increase with increasing w / c ratio, but decrease with increasing curing age. However, the recoverable creep/total creep ratio tends to decrease with increasing w / c ratio, but increase with increasing curing age, which indicates that more creep is recoverable in stiffer cement pastes. The logarithmic-type creep of cement pastes over the holding stage of microindentation tests can be characterized by a dashpot element with a variable viscosity that increases linearly with time. The initial viscosity seems to reflect the degree of polymerization of silicates in calcium silicate hydrate on the time when the external force is applied. The higher the initial viscosity is, the lower the creep potential of cement pastes is. It is also noted that the initial viscosity reveals a linear increasing relation with the curing age of cement pastes in log-log scale coordinates system.